Numerical Simulation of Pyroclastic Flow of Karangetang Volcano Based on 2015 Eruption Activity - Banggur, Willi FS; Patria, Cahya; Kriswati, Estu; Abdurrachman, Mirzam; Suantika, Gede; Syahbana, Devy Kamil; Korompis, Richard; Adriansyah, David; Gurasali, Aditya; Wenas, Alfred; Praja, Kurnia; Sentosa, Imam; Kusnadi, Iing; Shimomura, Makoto (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
On May 7-9, 2015 the eruptive activity of Mount Karangetang released pyroclastic flows towards the Batuawang River for 3.6 km and hit Kora kora village which is located south of the Main Crater. This pyroclastic flow originated from lava flows during the effusive eruption period. MODIS satellite image hotspot data shows the lava flow extrusion rate and total volume at the peak began to increase since April 2015 and continued to show an increase until December 2015, with the estimated volume and lava extrusion rate on  April 22, 2015 reaching 4.16x106 m3 and 0.53 m3/s, respectively, and on December 9, 2015 the volume reached 1.67x107 m3 with a lava extrusion rate of 1.97 m3/s. The results of field checks show that this pyroclastic flow is dominated by block and ash, and by using numerical simulations show the deflection of pyroclastic flow in accordance with the flow field of the Batuawang river, and the splash of pyroclastic flow towards Kora kora village in addition to the location adjacent to the river flow and also controlled by the narrowing of the river channel due to the accumulation of material in the flow field. A total of 8 numerical simulation cases have been carried out, and in our opinion with an input volume of 500 x103 m3 and a flow material friction of 0.5 is a case that corresponds to a flow event that reaches a distance of 3.6 km from the Main Crater.  Taking into account the current activity conditions we used the same parameters to estimate the area that could be affected by pyroclastic flows in the future. Numerical simulation show that the pyroclastic flow traveled 5 km in a south-southwest direction from the top of the main crater.